Tectonic analysis of regional potential field data. Issue 1 (1st December 2019) - Betts, Peter; Armit, Robin; Tiddy, Caroline; Armistead, Sheree; Ailleres, Laurent
Summary: This contribution uses several case studies to illustrate how regional aeromagnetic and gravity data is used to undertake tectonic analysis. Regional aeromagnetic and gravity data is a powerful tool for tectonic analysis because it can be interpreted and modelled at different scales, and it is very effective at imaging different crustal levels. The signal in the data can also be linked to geological features and processes, and importantly, it is amenable to structural analysis, which can be used to inform 3D geometry, kinematics, and overprinting relationships. When combined with geological context the data can constrain tectonic settings and evolutions, and importantly provide context for mineral system analysis. We use examples from the IOCG belts of Proterozoic Australia. We present data from the Mount Woods Inlier in the northern Gawler Craton, to this part of the craton is highly extended, resulting the development of a metamorphic core complex. We then illustrate the tectonic setting for IOCG mineralisation in the Curnamona Province, illustrating how structural analysis of the data provides key constraints on tectonic transport direction.